Extremism in contemporary Muslim life and the concept of Jama'ah - Ushama, Thameem (Islamic Cultural Centre, 2016)
Dogmatic religious extremism manifests itself much too frequently in Muslim communities today. This paper addresses that phenomenon to clarify relevant issues, especially the concepts of jamā'ah and Islamic leadership. Relevant verses from Scripture are compared with the patterns of living exemplified by the Prophet Muhammad, his companions and successors. The paper attempts to contrast authentic Islam with the concept of jamā'ah through references to sīrah and sunnah.